Does engagement partners' effort affect audit quality? With a focus on the effects of internal control system - Suyon Kim (Risks, 2021)
An audit team includes engagement partners, CPAs, and staff. Among them, partners play a vital role in performing tasks that require expertise and experience, such as analyzing and understanding the industry, and supervising the overall audit process. In detail, the partners establish an audit plan, determine the overall audit time, provide the audit input ratio of the engagement team, and review the audit reports. This study examines for association between the partner's audit hour ratio and audit quality depending on the client firms' characteristics. Although the role of partners is important, the information about partner audit hours is limited. However, the Korean government requires audit firms to disclose the partner hour information in the audit report starting in the 2014 fiscal year. By the disclosure, it is possible to examine the association between partner audit hours and audit quality. In this study, the information on partner audit hour is hand-collected from the firms' business reports. Using 6340 observations from 2014 to 2017, the partner audit hour ratio is associated with audit quality, under the characteristics of client firms. Firms' risks are adopted for client characteristics, and we focused on the operation of internal control. The internal control operation level is measured by the following: (1) the ratio of internal control personnel and (2) experience of the internal control personnel in the accounting and IT departments. The result suggests that for the firms where internal control is not effectively operated, partners make more effort to enhance audit quality.
Keywords: 330; partner’ s audit hour ratio; audit quality; internal control system